Numerical evaluation of galerkin finite volume solver for laminar/turbulent flow over flat plate - Namazi-Saleh, F. (Asian Research Publishing Network, 2016)
In this paper, attempts are made to use combination of numerical techniques to simulate fluid flow over a flat plate. The objective was not to investigate the physical phenomenon of flow in detail but to study numerical method as well as modeling aspects, which influence the quality of solutions. The incompressible Navier Stokes equations with large eddy simulation (LES) turbulence model were numerically solved to estimate velocity profile over surface of flat body exposed to current. The results are obtained by solving the incompressible form of the mass and momentum conservation equations using finite volume method. The near wall model and the subgrid scale (SGS) model plays an important role on modeling. Accordingly, proper boundary layer condition based on logarithmic velocity profile was imposed to capture turbulent velocity near to the wall. Several techniques such as local time steeping, residual smoothing and unstructured multigrid mesh were used to increase convergence acceleration. Results from large eddy simulation with Smagorinsky subgrid scale model are presented in two different types of flow such as laminar ant turbulent flow. All computed results are compared with Blasius solution or experimental data represented in literature. The results show good agreement with the aforementioned experimental and computational data. Imposing logarithmic law for velocity profile normal to the wall provide more accurate velocity profile in general especially for relatively coarse mesh. Â© 2006-2016 Asian Research Publishing Network (ARPN).